THE USE OF INDONESIAN FOLKTALE MOVIE TO TEACH NARRATIVE TEXT WRITING - Permatasari, Nur Indah; Suhartono, Luwandi; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe aim of the research is to find out whether Indonesian Folktale Movie is effective or not to teach narrative text writing. The research focused on the tenth grade students of SMK Negeri 1 Pontianak in academic year 2019/2020 by administering a written test about narrative text before and after giving two teaching treatment. The research applied Quasi-Experimental, in which the writer had one class for experimental and one class for control. The sample of this research was X AKL 3 as the experimental group and class X AKL 4 as the control group, which consist of 39 students in each class. The data was calculated and the results showed that the mean score of the experimental group students’ pre-test is 59.4, while the post-test is 79.71. The mean of control group students’ pre-test is 59.69, while the post-test is 61.79. The t-test was higher than the t-table (5.15 1.992). The result of the effect size (ES) was 3,34, which was categorized as a modest effect (ES>0.5). It proved that the alternative hypothesis was accepted. It can be concluded that the Indonesian Folktale Movie is modestly effective to teach students’writing narrative text. Keywords: Indonesian Folktale Movie, Narrative Text, Teaching Writing